Perkembangan Penelitian Penggunaan Artificial Intelligence di Perpustakaan Berbasis Data Scopus - Tupan, Tupan (Media Pustakawan, 2024)
This study aims to analyze the development of AI use in libraries with bibliometric methods based on Scopus data. The study uses bibliometric analysis methods. Data were collected from the Scopus database using the keywords (Artificial intelligence OR AI) AND (Library" OR Libraries)) AND (Limit-To ( Subjec Area, "Soci" ) ) AND ( Limit-To ( Language , "English" ) ) AND ( Limit-To ( Doc Type , "ar" ) ). The data were analyzed using the R-biblioshiny   and VOSviewer tools. The results of the study show that the trend of research on the use of artificial intelligence in libraries has increased significantly since 2020. The most widely used keywords in research on the use of artificial intelligence in libraries are artificial intelligence, machine learning academic libraries, libraries, ChatGPT, AI, library services, natural language processing, education information literacy and chatbots. The most productive main journals are Library Hi Tech News, Journal of Chemical Information and Modeling, Journal of Academic Librarianship, Library Hi Tech, Library Philosophy and Practice, and Electronic Library. The latest trending topics are AI literacy, electronic data interchange, intelligent libraries, library technologies, robotics in libraries, smart services, chatbots, ChatGPT, humanoid robot, large language models, library maching, library operations, library technology, openrefine, user experience, and research support. The results of this study can help libraries understand the direction of AI technology development to improve services.